Hospitalization rates in patients switched from oral anti-psychotics to aripiprazole once-monthly: final efficacy analysis. (February 2015) - Kane, John M.; Zhao, Cathy; Johnson, Brian R.; Baker, Ross A.; Eramo, Anna; McQuade, Robert D.; Duca, Anna R.; Sanchez, Raymond; Peters-Strickland, Timothy
Abstract Objective: To compare hospitalization rates in patients with schizophrenia treated prospectively with aripiprazole once-monthly 400 mg (AOM 400; an extended-release injectable suspension) vs the same patients' retrospective rates with their prior oral anti-psychotic therapy. Research design and methods: Multi-center, open-label, mirror-image, naturalistic study in a community setting in North America. Patients who required a change in treatment and/or would benefit from long-acting injectable anti-psychotic therapy were treated prospectively for 6 months with AOM 400. Retrospective data on hospitalization rates were obtained. Clinical trial registration: ClinicalTrials.gov: NCT01432444. Main outcome measures: The proportion of patients with ≥1 psychiatric inpatient hospitalization with oral anti-psychotic therapy examined retrospectively (months –4 to –1 before oral conversion) and after switching to AOM 400 (months 4–6 after initiating AOM 400). Results: Psychiatric hospitalization rates were significantly lower when patients were treated with AOM 400 compared with oral anti-psychotic therapy both in the 3-month primary efficacy sample (2.7% [n = 9/336] vs 27.1% [n = 91/336], respectively; p < 0.0001) and in the total sample (6-month prospective rate: 8.8% [n = 38/433] vs 6-month retrospective rate: 38.1% [n = 165/433]; p < 0.0001). Discontinuations due to adverse events (AEs) during cross-titration were lower in patients cross-titrated on oral aripiprazole for >1 and <4 weeks (2.9% [n = 7/239]) compared with patients cross-titrated for ≤1 week (10.4% [n = 5/48]). The most common treatment-emergent AEs during the prospective treatment phase were insomnia (6.7% [n = 29/431]) and akathisia (6.5% [n = 28/431]). Patient-rated injection-site pain decreased from the first injection to the last visit. Conclusions: In a community setting, patients with schizophrenia demonstrated significantly lower psychiatric hospitalization rates after switching from their prior oral anti-psychotic therapy to AOM 400. Patients served as their own control, and thus an active control group was not included in this study. Confounding factors, such as insurance coverage and availability of hospital beds, were not examined here and deserve further consideration.